Anomalous thermoelectricity of pure ZnO from 3D continuous ultrathin nanoshell structures. Issue 6 (29th January 2018) - Kim, Kisun; Park, Junyong; Hong, Seokkyoon; Park, Sun Hwa; Jeon, Seong Gi; Ahn, Changui; Song, Jae Yong; Jeon, Seokwoo
Abstract : A new concept for realizing 3D nanostructured thermoelectric materials with greatly enhanced performance. Abstract : ZnO is a potential thermoelectric material because of its non-toxicity, high thermal stability, and relatively high Seebeck coefficient ( S ) of metal oxides. However, the extremely low figure of merit ( zT ), which comes from a high thermal conductivity ( κ ) over 40 W m −1 K −1, limits the thermoelectric application of ZnO. In particular, below 500 K, ZnO exhibits a nearly negligible zT (<10 −3 ), unless a dopant is incorporated into the crystal structure. Here, we propose a new strategy for achieving a reduced κ and a correspondingly increased zT of pure ZnO over a wide temperature range from 333 K to 723 K by forming an ∼72 nm thick, 3D continuous ultrathin nanoshell structure. The suppressed κ of the 3D ZnO film is ∼3.6 W m −1 K −1 at 333 K, which is ∼38 times lower than that of the blanket ZnO film (3.2 μm thick), which was set as a reference. The experimental zT of the 3D ZnO film is ∼0.017 at 333 K, which is the highest value among pure ZnO reported to date and is estimated to increase by ∼0.072 at 693 K according to the Debye–Callaway approach. Large-area (∼1 in 2 ) fabrication of the 3D ZnO film with high structural uniformity allows the realization of an integrated thermoelectric device, which generates ∼60 mV at a temperature difference of 40 K along the in-plane direction.